2013
DOI: 10.7314/apjcp.2013.14.11.6249
|View full text |Cite
|
Sign up to set email alerts
|

Folate-Related Nutrients, Genetic Polymorphisms, and Colorectal Cancer Risk: the Fukuoka Colorectal Cancer Study

Abstract: Asian Pac J Cancer Prev, 14 (11), [6249][6250][6251][6252][6253][6254][6255][6256] IntroductionThe one-carbon metabolism has drawn considerable attention in relation to colorectal carcinogenesis (Ulrich, 2005;Hubner and Houlston, 2009;Williams, 2012). A folate metabolite, 5-methyl tetrahydrofolate (THF), provides the methyl group in the reaction by methionine synthase (MTR) to convert homocysteine to methionine, the precursor of S-adenosylmethionine (SAM). The SAM is the universal methyl-group donor for methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…B vitamins, including folate, vitamin B6, and vitamin B12, play an important role in the metabolism of coenzymes in one-carbon units, and they are also important in DNA synthesis, repair, and methylation (Ulrich, 2005). Previous studies have indicated a potential association between folate intake and other vitamins and risk of several cancers, such as oral and pharyngeal cancer, breast cancer, colorectal cancer, and esophageal cancer (Bravi et al, 2013;Liu et al, 2013;Morita et al, 2013;Sharp et al, 2013). For breast cancer, a recent metaanalysis showed high folate intake did not protect against breast cancer development (Castillo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…B vitamins, including folate, vitamin B6, and vitamin B12, play an important role in the metabolism of coenzymes in one-carbon units, and they are also important in DNA synthesis, repair, and methylation (Ulrich, 2005). Previous studies have indicated a potential association between folate intake and other vitamins and risk of several cancers, such as oral and pharyngeal cancer, breast cancer, colorectal cancer, and esophageal cancer (Bravi et al, 2013;Liu et al, 2013;Morita et al, 2013;Sharp et al, 2013). For breast cancer, a recent metaanalysis showed high folate intake did not protect against breast cancer development (Castillo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies have assessed vitamin B2 intake only from food sources and did not take into account intake from supplemental sources . Only a few studies evaluated the associations between total vitamin B2 intake including supplements or supplemental vitamin B2 intake itself and CRC risk.…”
mentioning
confidence: 99%
“…1 Despite these mechanisms suggesting a potential role of B2 in colorectal carcinogenesis, epidemiological studies have been inconsistent. In contrast to null findings from most individual cohort studies [2][3][4][5][6][7][8] and case-control studies, [9][10][11][12][13][14][15][16][17] a recent metaanalyses found significant inverse association between vitamin B2 intake and risk of colorectal cancer (CRC) from four casecontrol studies [pooled odds ratio (OR) 5 0.78, 95% confidence interval (95% CI): 0.66-0.91 for highest vs. lowest categories of intake of vitamins B2] and from five prospective cohort studies (pooled OR 5 0.86, 95% CI: 0.76-0.97). 18,19 These suggest that limited statistical power might have been a reason for the null associations in individual studies.…”
mentioning
confidence: 99%
“…Calcium appears to have anti-tumor activities and previous studies have indicated that dietary calcium may protect against the risk of colon cancer development or act as a confounding factor (Sesink et al, 2001;Galas et al, 2013;Morita et al, 2013). Calcium is involved in cell proliferation and differentiation and decreases colonic epithelial cell proliferation (Buset et al, 1986).…”
Section: Introductionmentioning
confidence: 99%